Drug‐induced hepatotoxicity: incidence of abnormal liver function tests consistent with volatile anaesthetic hepatitis in trauma patients. (15th August 2013) - Lin, Jonathan; Moore, David; Hockey, Brad; Di Lernia, Rachel; Gorelik, Alexandra; Liew, Danny; Nicoll, Amanda
Abstract Background & Aims Volatile anaesthetic drug‐induced liver injury can range from asymptomatic alanine transaminase elevations to fatal hepatic necrosis. There is very limited research regarding hepatotoxicity of modern volatile anaesthetic agents. The aim of this study was to determine how common liver injury consistent with volatile anaesthetic hepatitis is, following exposure to isoflurane, desflurane and sevoflurane; and to propose risk factors for its development. Methods Following ethics approval, we conducted a retrospective audit of adult trauma patients with abnormal liver biochemistry following volatile anaesthesia during January 1 to December 31, 2009. The data collected included patient demographics, volatile anaesthetic administration, concurrent medication, perioperative liver biochemistry results and comorbidities. The Council for International Organisations of Medical Sciences/Roussel Uclaf Causality Assessment Method scoring system was used to group cases according to the likelihood of volatile anaesthetic being the causative agent of drug‐induced hepatotoxicity. Results Forty‐seven (3%) of 1556 patients had abnormal post‐operative liver biochemistry potentially attributable to volatile anaesthetic. Of the 47, 12 patients (26%) had peak alanine transaminase levels greater than 200 U/L. No significant predictors of volatile anaesthetic drug‐induced liver injury following isoflurane, desflurane or sevoflurane anaesthesia could be identified. Conclusion Volatile anaesthetic drug‐induced liver injury in adult trauma patients may be significantly more common than previously noted. This study suggests that about a quarter of patients with volatile anaesthetic drug‐induced liver injury develop significant liver injury. Further prospective studies are required to define risk factors and clinical outcomes.